MEMBANGUN HARMONISASI DENGAN BEDA AGAMA - Ali Halidin (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2018)
Generally, diversity in religioun and in a pluralistic society, for Indonesia people, the discourse and though of religion and multiculturalism is always challenging. And handling the diversities, because religious diversity could create either conflict or harmony, depending on how do we perceive the meaning of religious diversity and pluralism. The pluralism, is going to the important thing to be convest by indonesian people, If religious diversity is perceived as a threat, it is possible to create tension and conflict between religions. In contrast, and the reality of social disadvantage it would contribute to disseminate tolerant and harmony. And also the ortthodoksi that had been done by the people shown the religioun had good situation in Indonesia. It is necessary therefore to strengthen the concept of multicultural education with religious values. The author observes the concept of multicultural education from the perspective of religions